Comparison of tensile strength and fracture toughness under mode I and II loading of co-cured and co-bonded CFRP joints - F. Moroni; A. Pirondi; C. Pernechele; A. Gaita; L. Vescovi (Fracture and Structural Integrity)
Carbon-Fiber Reinforced Polymer (CFRP) parts are joined mainly using adhesive bonding because, differently from fastening, additional parts (hence weight saving) and through holes (that are always detrimental for the strength due to the possibility of developing damage into the composite) are not necessary. Additionally, it allows for large connection areas, thus distributing stresses better than fastened connections. However, since CFRP can be joined by co-curing, the choice of bonding has to be evaluated as an alternative by a trade-off in terms of strength and durability, compared to cost and manufacturing time and complexity. In this work, a comparison between co-cured and co-bonded CFRP is done with respect to tensile strength and mode I and mode II fracture toughness, in order to understand whether cobonding guarantees the same performance of a co-cured composite part